Substance use and disordered eating risk among college students with obsessive-compulsive conditions - Wura Jacobs; Angela DeLeon; Alane Bristow; Patrick Quinn; Alyssa Lederer (PLoS ONE, 2025)
Purpose College students are at higher risk for problematic substance use and disordered eating. Few studies have examined the comorbid risks associated with OCD despite the increased prevalence of OCD among young adults. This study examined substance use and disordered eating risk associated with OCD conditions among college students and how this association may vary by sex/gender. Methods Data were from 92,757 undergraduate students aged 18–24 enrolled in 216 colleges between Fall 2021 and Fall 2022, from the American College Health Association-National College Health Assessment III. Regression models were used to estimate alcohol, cannabis, tobacco, and disordered eating risk among those with OCD related conditions compared to those without conditions, overall and by sex/gender, while adjusting for covariates and school clustering. Results Students with OCD conditions displayed a higher prevalence of substance use and disordered eating risks. In adjusted models, OCD conditions were associated with increased odds of moderate/high tobacco (aOR = 1.12, 95% CI 1.05, 1.21), cannabis (aOR = 1.11, 95% CI 1.04, 1.18), alcohol (aOR = 1.14, 95% CI 1.05, 1.24) and disordered eating risk (aOR = 2.28, 95% CI 2.13, 2.43). Analyses stratified by gender revealed cis-female students with OCD conditions were at increased risk for moderate/high risk alcohol (aOR = 1.18, 95% CI 1.08, 1.29), tobacco (aOR = 1.12, 95% CI 1.03, 1.22), cannabis (aOR = 1.13, 95% CI 1.06, 1.23) and disordered eating (aOR = 2.30, 9%% CI 2.14, 2.47). Among TGNC students, OCD conditions were associated with increased risk for moderate/high tobacco risk (aOR = 1.24, 95% CI 1.05, 1.48) and disordered eating (aOR = 2.14, 95% CI 1.85, 2.47). OCD conditions was only associated with disordered eating among male students (aOR = 2.34, 95% CI 1.93, 2.83). Discussion Young adult college students with OCD conditions exhibit a higher prevalence of medium/high risk alcohol, tobacco, and cannabis use and disordered eating compared to their counterparts without such conditions, even after adjusting for stress, depression, and anxiety.